MOTIVASI AUSTRALIA MELAKUKAN KERJA SAMA DI BIDANG INFRASTRUKTUR DENGAN ASEAN PADA TAHUN 2018 - Zulvia, Mega; Olivia, Yessi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The purpose of this research is to explain the motivation of Australia to pursue collaboration with ASEAN on infrastructure. In early 2018, ASEAN held its first summit in Sydney, Australia. This summit resulted with an agreement between Australia and ASEAN to improve infrastructure development in the ASEAN countries. This is an interesting topic to research because this summit was the first ASEAN’s event held in Australia. To explain Australia’s motivation, this research examines Australia's interest in the Asia Pacific region and focuses on Australia’s engagement with ASEAN.The research uses a qualitative method with document analysis technique. Data for this research is taken from books, scientific journals, magazines, newspapers, and the Internet. The research built on the perspective of neorealism in the study of International Relations which assume that the structure of the international system influences the behavior of states. This research uses the nation-state level analysis, and applies the balance of power theory, in particular hedging strategy to analyze Australia’s interest in pursuing cooperation with ASEAN.This study shows that Australia's motivation to collaborate in the infrastructure sector with ASEAN in 2018 is part of Australia’s strategy to balance China's growing influence in the Asia Pacific region. That Australia's strategy can be interpreted as a form of hedging strategy, which Australia balances the power through their infrastructure cooperation relationship with ASEAN in a situation full of uncertainty and risk due to the strengthening of China's influence in the Asia Pacific region. In addition, the anticipation of the rise of China's power was carried out by Australia by carrying out the Indo-Pacific strategy which was stated directly in Australia’s Defense White Paper in 2013, with the implementation of Southeast Asia as the geographic center of the Indo-Pacific region. Australia's implementation of the Indo-Pacific strategy uses instruments such as ASEAN and the EAS to shows the important role of Indo-Pacific engagement in ASEANKeywords: Australia, ASEAN, international cooperation, hedging strategy, motivation